Pharmaceutical characterization and pharmacokinetics of florfenicol-loaded alginate dried beads in rabbits - Lilia Gutierrez Olvera; Xelhua Marcos Benitez; Perla García-Guzmán; Minerva Monroy-Barreto; Héctor Sumano (World Rabbit Science, 2022)
The pharmacokinetic variables of a new formulation of florfenicol included in dried bean of alginate (FADBs), its acceptance as in food medication, and its relationship with theoretical minimum inhibitory concentration (MIC) values of the main pathogens in rabbits, are presented. FADBs sought to mask the unpleasant taste of florfenicol while enhancing sustained absorption in a day to facilitate and optimise its dosage in this species. The entrapment efficiency was determined to be 94-98% and 73.56±3.26% of drug loading. No reduction in food consumption was detected, nor selectivity when choosing from their usual food. The elimination half-life was 1.23 to 2.4 h slower than the one previously reported in the literature. Possible flip-flop pharmacokinetics is proposed for FADBs in rabbits, thus complying better with the key pharmacokinetics/pharmacodynamics (PK/PD) ratio of t≥MIC. Also, if a MIC2.0 μg/mL is taken as the cut-off point for florfenicol in rabbits, then ad libitum intake of FADBs in their standard diet is sufficient to maintain plasma concentrations of florfenicol above this level during the whole dosing interval of 24 h. Additionally, FADBs are a low-cost and attractive drug delivery system for the oral controlled release of florfenicol in rabbits.